MaqÄá¹£id al-SharÄ«â€™ah on Wakaf System - Susanto, Heru (Hunafa: Jurnal Studia Islamika, 2017)
The main purpose of the shariah is realizing the benefit in order to maintain the shariahâ€™s purposes. There are three level of humanâ€™s basic necessity: primary (á¸arÅ«riyyÄt), secondary (hÄjiyyÄt), and tertiary (taá¸¥sÄ«niyyÄt). The humanâ€™s basic necessity is divided into five, first, protection of religion (á¸¥ifáº“ al-dÄ«n), second, protection of life (á¸¥ifáº“ al-nafs), third, protection of mind (á¸¥ifáº“ al-â€˜aql), fourth, protection of the offspring (á¸¥ifáº“ al-nasl), and fifth, protection of property (á¸¥ifáº“ al-mÄl). So it can be said that the aims of shariah can be achieved by fulfilling these five basic necessities of human beings. Waqf as one of the Islamic filantrophies has a big role and purpose to realize the benefit of human being, that is realizing the prosperity reflected by the fulfilment of humanâ€™s basic needs in accordance with the goals of shariah be it primary, secondary and tertiary.